From the Foundations to the Legacy of Minoan Archaeology : Studies in Honour of Professor Keith Branigan - Relaki, Maria (Sheffield Studies in Aegean Archaeology Ser., 2018)
Cover -- Book Title -- Copyright -- Contents -- Preface -- List of contributors -- 1. Keith Branigan: Introductory: Peter Warren -- 2. Roots and routes: Technologies of life, death, community and identity: Maria Relaki -- 3. Inspecting the foundations: The Early Minoan Project in review: Peter Tomkins -- 4. Early Minoan Knossos: A few new thoughts: Gerald Cadogan -- 5. Caves in Crete and their use as architectural space: Philip P. Betancourt -- 6. Mortuary variability, social differentiation and ranking in Prepalatial Crete: The evidence from the cemetery of Phourni, Archanes: Yiannis Papadatos -- 7. Variables and diachronic diversities in the funerary remains of the Kamilari tholos tombs: Luca Girella -- 8. Managing with death in Prepalatial Crete: The evidence of the human remains: Sevi Triantaphyllou -- 9. The house tomb in context: Assessing mortuary behaviour in north-east Crete: Ilse Schoep -- 10. Visible and invisible death. Shifting patterns in the burial customs of Bronze Age Crete: Eleni Hatzaki -- 11. Recognising polities in prehistoric Crete: Todd Whitelaw -- 12. The relevance of survey data as evidence for settlement structure in Prepalatial Crete: Donald C. Haggis -- 13. Comparative issues in archaeological field survey in the Asterousia region: Andonis Vasilakis and Kostas Sbonias -- 14. Beyond the collective … The Minoan Palace in action: Jan Driessen -- 15. The "emergence of the individual" revisited: Memory and trans-corporeality in the mortuary landscapes of Bronze Age Crete: Yannis Hamilakis -- Back Cover